Monitoreo en tiempo real del hato bovino de la universidad Técnica Estatal de Quevedo en la finca la María, año 2014 - Samaniego Mena, Eduardo Amable (2015)
On the La María farm of the Técnica Estatal University of Quevedo, automatic systems are not implemented in the processes for sanitization control during animal production, which results in the loss of information, causing a great difficulty when identifying the cattle. Since there is no system that conducts the sanitization control of the cattle, it is difficult to prevent its diseases. At the same time there is no location control of the livestock which causes losses. The information obtained about the conditions of the cattle is carried out by hand, as a result the information is lost or there are delays in the interpretation of reports obtained from that data. The objectives of the research attempt to determine the viability of the implementation of a system to control the cattle on La María farm as well as to make use of wireless communication technologies to monitor livestock in real time, which leads us to establish that by using these technologies an incidence of the cattle control done on La María farm as hypothesis. Due to the lack of a system that permits to control and make decisions on the cattle processes carried out on the farm, it is proposed here the implementation of a prototype to collect data through communication technologies that allow to monitor the cattle in real time, with which we wish to show the university community that by means of technological practice of high quality we can go through the path of excellence in research. In order that the aforementioned processes are carried out, a positioning control of the cattle by monitoring in teal time is used through GPS technologies, which has a data transfer of 171.2 kbps, with a range of 1609000 meters since it works using satellite range. Research techniques are also used which allow us to collect the necessary information to run statistical analysis that is conducive of viable study of the research project. With this study we pretend to automatize the sanitization processes of the cattle conducted on La María farm as well as to involve the community of the university into those processes related to the field of technology and cattle breeding